2009
DOI: 10.3727/108354209x12597959359130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Historical Districts: Exploring the Use of Photographs and Slide Experiments

Abstract: This study explores approaches and methods to investigate visitors' evaluation of historical districts. Personal interviews with use of repertory grid analysis and laddering analysis and slide experiments with photographs were conducted with a sample of students to reveal relationships between various evaluative components. The results of the two sets of methods are examined in a comparative manner to obtain abundant insights into evaluations of historical districts and the efficacy of these methods. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…They concluded that the presence of other people discourages visitors' unique experiences and sense of the famous, touristic, and novel atmospheres. Naoi, Airey, and Iijima (2009) found results similar to Naoi et al (2007) using slide experiments. Aikoh et al (2002) investigated the effects of the number of people in photographs of a nature tourist attraction and found that the number of people in the photographs positively related to perceptions of crowding.…”
Section: The Effects Of People On Evaluations Of Historic Districtssupporting
confidence: 83%
See 4 more Smart Citations
“…They concluded that the presence of other people discourages visitors' unique experiences and sense of the famous, touristic, and novel atmospheres. Naoi, Airey, and Iijima (2009) found results similar to Naoi et al (2007) using slide experiments. Aikoh et al (2002) investigated the effects of the number of people in photographs of a nature tourist attraction and found that the number of people in the photographs positively related to perceptions of crowding.…”
Section: The Effects Of People On Evaluations Of Historic Districtssupporting
confidence: 83%
“…Photographs have been found to depict environments more accurately than written descriptions (Brown, Richards, Daniel, & King, 1989;Munson, 1993). Slide experiments have been used in previous studies of evaluations of tourist attractions (MacKay & Fesenmaier, 1997, 2000, historic districts as tourist attractions (Naoi & Iijima, 2004;Naoi et al, 2009), and tourist sites (Miyaji, Nishina, Tanaka, & Yoshihara, 2011).…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations